DNA–polyfluorophore excimers as sensitive reporters for esterases and lipases() - Dai, Nan (Chem Commun (Camb), 2010)
DNA-scaffolded oligodeoxyriboside fluorophores (ODFs) were used as the reporters in turn-on sensing of enzymatic bond-cleaving activity. A tetramer ODF of pyrene deoxynucleosides displayed high quenching efficiency when conjugated via ester linkages with a dabcyl quencher, and yielded large signal increases with several enzymes in vitro and in intact human cells.